Product design and innovation: manufacturing SMEs in Santiago de Chile - Méndez Reátegu, Rubén (2022)
This descriptive review paper has been developed from an interdisciplinary approach. It focuses on the essence of the contribution and impact of design in permanent collaboration with economic science, both in its theoretical conception and application in the company. The authors whose works were revised for this paper, declare design as a project activity from areas such as entrepreneurship, creativity and innovation, which are essential for the change of the productive matrix, taking Chile as a study reference. It is concluded that design is a projective discipline that manages creative processes within the company in order to introduce concepts of innovation that directly affect the product, and from there to develop strategic content in SMEs that facilitate the work of the entrepreneur in guiding added-value processes that generate opportunities for expansion and growth in the market.